Determining Operations Strategy for KPC Melawan Coal Handling Plant - Praptono, ES Heru; Yudoko, Gatot (The Indonesian Journal of Business Administration, 2015)
Abstract. PT KPC have goal to reach 70 MTPA (million ton per annum) productions in 2017. Plant expansions have been done to fit the infrastructure to that goal.  KPC Melawan CHP (Coal Handling Plant) with Overland Conveyor has been built to increase crushing capacity and reduce energy consumption. The plant will be handed over to operation in July 2015. Melawan CHP expected reach sustain capacity of 30 MTPA.  The operations strategy for new plant should be set for the course of action over time for a long-term capability of operation. To determine operations strategy, it’s started by evaluating gap between the existing with new plant in order to gain information to identify problems based on structural and infrastructural decision area. Root causes examined using CRT (Current Reality Tree). From CRT exercise, the identified root causes are inappropriate structural and infrastructural operations strategy decisions. Core problem from those root causes is Unadjusted existing operations strategy to be used for the Melawan CHP. Business solution part start with visit existing strategy maps to recognize required performance objective that not yet covered. Adjusted strategy objectives is to ensure the sustain coal production, that flexible to marketing requirement which supported by four decision areas consist of capacity, supply network, process technology, and development & organization. Five performance objectives are combined with those decision areas to generate operation strategy matrix. After finding operations strategy in the matrix, existing Balance Scorecard and Strategy Map are adjusted and additional strategy initiatives are developed. The critical strategies are reliable throughput, controlled quality, clarity in cost, and production planning ‘fit’. Future Reality Tree (FRT) was used as decision tools to determine the best strategy using the ‘injection’ of new initiatives to eliminate root causes.  To implement the proposed solution, company should focus on internal capabilities to translate operations strategy into operational task. Hence, operations strategy is emphasized in internal-external and financial-non financial factor balancing.  Keywords: Operation Strategy, Current Reality Tree, Balanced Scorecard, Strategy Map, Future Reality Tree.